Comparing the association between social capital and self-rated health in poor and affluent nations - William T. Story; Jennifer L. Glanville (Elsevier, 2019)
Country context has been shown to influence the association between social capital and health; however, few studies have examined how the level of societal affluence affects the relationship between social capital and health. Drawing on the study of individual-level socioeconomic variation in the returns to social capital by Uphoff and colleagues (2013), we examine two possible explanations about the differential impact of social capital on health based on country-level socioeconomic variation. The buffer hypothesis posits that social capital will have a greater benefit for poorer (versus more affluent) nations, whereas the dependency hypothesis suggests that social capital will be more beneficial in more affluent (versus poorer) nations. Using Waves 5 and 6 of the World Values Survey, we employed multilevel ordered logistic regression to examine whether national wealth moderates the association between social capital-as measured by particularized and generalized trust-and self-rated health across 72 countries. We also assessed five potential explanations for the moderating role of economic context based on the buffer and dependency hypotheses: institutional effectiveness, economic inequality, coverage of health services, human capital, and access to clean water and sanitation services. In support of the dependency hypothesis, we found that both particularized and generalized trust were associated with self-rated health to a greater extent in more affluent countries than in poorer countries; however, none of the potential explanations that we tested accounted for this pattern. Further, we found that particularized trust was more strongly associated with self-rated health compared to generalized trust across all countries. Future research should focus on the mechanisms by which economic context modifies the relationship between social capital and self-rated health. Keywords: Social capital, Trust, Self-rated health, Low- and middle-income countries, Gross domestic product (GDP)